The Effect of Nano Chitosan Xylotrupes Gideon on Fibroblast Proliferation and Collagen Deposition in the Oral Mucosa of Rattus norvegicus - Komariah Komariah; Muhammad Orliando Roeslan; Rezky Anggraeni; Didi Nugroho Santosa; Aubrey Kanya Rennata (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Lacerations of the oral mucosa are a common clinical problem and require an efficient healing process. The wound healing process involves the haemostasis, inflammation, proliferation, and maturation phases. During the proliferation phase, fibroblasts play an important role in migration and proliferation to produce collagen, which connects the wound's edges and provides strength and stability to the scar tissue that forms. Chitosan from the horned beetle (Xylotruphes gideon) contains active compounds that are thought to accelerate the healing process by increasing the activity of inflammatory cells and fibroblast proliferation. Physical modification into nanoparticles facilitates penetration into the mucosal layer, thereby accelerating collagen production and re-epithelialization. This study aimed to determine the effect of X. gideon nanokitosan administration on increasing fibroblast proliferation and collagen formation in vivo. The study was divided into five groups: positive control, negative control, and nano chitosan treatment at 3000, 1500, and 750µg/mL. All groups of experimental animals were previously given an injury to the right cheek mucosa with a No. 12 scalpel blade, and nano chitosan was administered topically. The increase in fibroblasts and collagen deposits was determined by HE and Masson's Trichrome staining on days 3, 7, and 14, which were observed microscopically and using ImageJ. The results showed a significant increase in fibroblasts on day 3 and collagen fibre deposition on day 14 in all treatment groups. The group with 750 ppm nano chitosan showed the best results in accelerating wound healing regarding fibroblast proliferation and collagen deposition. Conclusion: Nano chitosan X. gideon at a concentration of 750 ppm effectively accelerates wound healing in the cheek mucosa of mice by increasing fibroblast proliferation and collagen deposition.